Characterising the role of potential accessory factors that facilitate secretion and gene regulation of the EspC and AaaA autotransporters - Alhagh, Mohammad Shakib (2021)
Entropathogenic Escherichia coli (EPEC) is one of the major causes of death from infantile diarrheal-related illness in children under 2 years old. EspC, is an Extracellular Serine Protease Autotransporter (AT) belonging to the Enterobacteriaceae (SPATE) superfamily that is highly immunogenic. It is secreted via the type Va classical secretion system which relies on a C-terminal transporter domain that forms a β-barrel in the outer membrane during translocation before being cleaved to release the functional protease (passenger domain). EspC can act as an Enterotoxin, Iron-binding protein and have a cytopathic effect on the host cells. The complete mechanism of EspC secretion, pathogenesis, interaction with the type III secretion system and the role of accessory factors is not completely known. In this study, to better understand the molecular pathway of EspC secretion, plasmids encoding full length native EspC, or EspC fused to mCherry in the presence or absence of the β-barrel transporter were inserted into putative AT secretion accessory factor mutants (ΔproW, ΔslyB, ΔsapA, ΔybgC, ΔyqjE and ΔabrB). To investigate the resultant localization patterns, immunoblot analysis and fluorescent microscopy were performed. It appears that the β-barrel transporter domain plays an important role in the localization of the EspC secretion pattern since in its absence EspC-mCherry was diffusely distributed, rather than organised at the poles of the bacteria. Analysis of a mutant strain of MG1655 defective in SlyB (ΔslyB) showed clear morphological differences to the wild type strain. The ΔslyB mutant of MG1655 did not produce any detectable EspC-mCherry when attached to the β-barrel transporter and released more truncated EspC-mCherry compared to parental E. coli MG1655. To rule out any pleotropic effects, the ΔslyB mutant was genetically complemented by introducing engineered plasmids encoding either native SlyB, or a version of SlyB containing a His-tag. No significant difference was observed in terms of EspC stability and secretion between the mutated and complemented strains, casting doubt about a role of SlyB as an accessory factor in EspC secretion. Pseudomonas aeruginosa is an opportunistic pathogen, metabolically adaptable bacterium with diverse antibiotic resistance mechanisms that can cause hospital-associated infections in immunocompromised and cystic fibrosis (CF) patients. The PA0328 autotransporter was identified as a cell-surface tethered autotransporter with arginine-specific aminopeptidase activity and named: arginine-specific autotransporter of P. aeruginosa (AaaA). Previous studies suggested the dynamic spiral localization of EspC during secretion is shared by the autotransporter AaaA. Here, the same investigative approach has been employed to track AT secretion using a fluorescent tagging technology that relies on a small tetracysteine motif (FlAsH) engineered into the AT rather than having a fusion of the AT to the larger mCherry fluorescent protein, to see if this affected the function of SlyB. To do this, immunoblot analysis and confocal microscopy were performed on the parental MG1655 and ΔslyB mutant strains producing either AaaA or EspC tagged with FlAsH. EspC and AaaA were identified as large 173 kDa and 80 kDa proteins respectively and were distributed in a similar pattern in both WT and ΔslyB MG1655 cells, irrespective of the presence of the β-barrel transporter for both AaaA and EspC.